REGULATORY MODEL FOR THE UTILIZATION OF LAND BANK MECHANISMS IN INDONESIA TO PREVENT AND AVOID LAND MAFIA PRACTICES: A COMPARATIVE STUDY BASED ON LAND GOVERNANCE - Putri Purbasari R.M.; Delarosa, Stella (Universitas Katolik Indonesia Atma Jaya, 2025)
The issue of the